144 Growth Factors Influence Cell Cycle Progression in Equine Satellite Cells. (1st March 2018) - Gonzalez, M; Brandt, A M; Johnson, S E
Abstract: Adaptation of skeletal muscle to exercise is partially mediated by satellite cells (SCs) residing near the myofiber. Exercise stimulates production of growth factors (GF) that induce SCs to enter the cell cycle, differentiate, and fuse to the nearby myofiber. Growth factors responsible for entry of equine SCs (eqSCs) into the cell cycle are unknown. The objective of the study was to examine the effects of GFs expressed by skeletal muscle on eqSCs time to S-phase entry in vitro. Biopsies were obtained from the gluteal muscle of mature thoroughbred geldings (n=8), eqSCs isolated, and myogenicity confirmed. Following 24 h attachment to an entactin-collagen-laminin matrix, eqSCs were washed exhaustively and incubated with Dulbecco's Modified Medium containing 1% fetal bovine serum, 1% penicillin-streptomycin, and 0.2% gentamicin supplemented with either 10 ng/mL Epidermal GF (EGF), 10 ng/mL Fibroblast GF-2 (FGF-2), 25 ng/mL Hepatocyte GF (HGF), 100 ng/mL IGF-1, 10 ng/mL IGF-2, 10 ng/mL IL-6, or an equivalent amount of 0.1% BSA. Parallel plates were maintained and cells co-incubated with 5-ethynyl-2'-deoxyuridine (EdU), a thymidine analog, for 2 h prior to fixation at either 0, 24, 48 or 72 h post-treatment. Incorporation of EdU was detected by click chemistry (AlexaFluor 488 EdU Detection kit; ThermoFisher) and total nuclei detected by Hoechst 33342. Epifluorescent micrographs were obtained and the percentage of cells in S-phase calculated as (number of EdU positive)/(number of nuclei) x 100. Results were analyzed by ANOVA with Tukey's posthoc adjustment using the GLM procedure of SAS. As time in culture progressed, the percentage of EdU positive eqSC increased from 0 ± 0.85 % at 0 h post-treatment to 11.65 ± 0.85 and 34.71 ± 0.85% at 48 and 72 h post-treatment, respectively ( P < 0.0001). At 48 h in treatment, only IGF-2 (14.42 ± 0.89) increased ( P = 0.05) the percentage of cells in S-phase compared to control (10.54 ± 0.89). After 72 h in treatment, FGF-2 (40.34 ± 1.65) and HGF (41.73 ± 1.65) increased ( P < 0.0004) the percentage of cells in S-phase relative to control (29.19 ± 1.65). Control and IGF-2 treated cells were not different 72 h post-treatment. These results indicate that following isolation, adult eqSCs require 72 to 96 h to enter S-phase of the cell cycle irrespective of treatment. Of the GF tested, only IGF-2 accelerated entry into S-phase while FGF-2 and HGF served as mitogens at 72 h.